Analysis of class I and II histone deacetylase gene expression in human leukemia. Issue 12 (2nd December 2015) - Yang, Hui; Maddipoti, Sirisha; Quesada, Andres; Bohannan, Zachary; Cabrero Calvo, Monica; Colla, Simona; Wei, Yue; Estecio, Marcos; Wierda, William; Bueso-Ramos, Carlos; Garcia-Manero, Guillermo
Abstract : Histone deacetylase (HDAC) inhibitors are well-characterized anti-leukemia agents and HDAC gene expression deregulation has been reported in various types of cancers. This study sought to characterize HDAC gene expression patterns in several types of leukemia. To do so, a systematic study was performed of the mRNA expression of all drug-targetable HDACs for which reagents were available. This was done by real-time PCR in 24 leukemia cell lines and 39 leukemia patients, which included AML, MDS and CLL patients, some of whom received HDAC inhibitor treatment. Among the samples analyzed, there was no discernible pattern in HDAC expression. HDAC expression was generally increased in CLL patients, except for HDAC2 and HDAC4. HDAC expression was also generally increased in VPA-treated MOLT4 cells. However, this increased expression was not seen in AML patients treated with vorinostat. In summary, increased HDAC expression was noted in CLL patients in general, but the HDAC expression patterns in myeloid malignancies appear to be heterogeneous, which implies that the role of HDACs in leukemia may be related to global expression or protein function rather than specific expression patterns.